2021
DOI: 10.1097/aco.0000000000001017
|View full text |Cite
|
Sign up to set email alerts
|

Ready for a “breakthrough” with ketamine? A look at recent pharmacological insights!

Abstract: Purpose of reviewTo update pharmacological insights on ketamine integrating information from different disciplines for developing steps to ''breakthrough'' approaches in clinical challenges. Recent findingsPharmacokinetic/pharmacodynamic (PK/PD) models have incorporated recirculation, ketamine metabolites, drug-drug interaction, and covariates such as age. Ketamine-induced relief from treatment-resistant depression has been explained by ''disinhibition'' of gamma-aminobutyric acid-ergic interneurons and synapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 91 publications
1
8
0
Order By: Relevance
“…54,56 We found an agonist/ partial agonist interaction of subanesthetic dose ketamine isomers in the racemate. 24 As expected, clinical studies that focused on arousal after anesthesia/ sedation reported shorter time frames after es- versus racemic ketamine 19,25,28,30,57 (Table 2). Table 4 summarizes pharmacological effects of esketamine compared to the racemate.…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…54,56 We found an agonist/ partial agonist interaction of subanesthetic dose ketamine isomers in the racemate. 24 As expected, clinical studies that focused on arousal after anesthesia/ sedation reported shorter time frames after es- versus racemic ketamine 19,25,28,30,57 (Table 2). Table 4 summarizes pharmacological effects of esketamine compared to the racemate.…”
Section: Resultssupporting
confidence: 63%
“…There was no measurement of drug plasma concentration although esketamine undergoes extensive metabolism. 24,49 Some of the multiple active metabolites even exert own analgesic action without psychedelic effects. 5…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations